Doenjang, A Korean Traditional Fermented Soybean Paste, Ameliorates Neuroinflammation and Neurodegeneration in Mice Fed a High-Fat Diet - Ko, Je Won (Nutrients, 2019)
Obesity is considered a risk factor for neurodegeneration. Because fermentation of soybean increases contents of various bioactive compounds with anti-obesity and anti-diabetic activities, we investigated the protective effect of doenjang, a Korean traditional fermented soybean paste, against neuroinflammation and neurodegeneration in the cortex and hippocampus of mice fed a high-fat (HF) diet. C57BL/6J mice were fed a low-fat diet, an HF diet, an HF-containing steamed soybean diet, or an HF-containing doenjang (DJ) diet for 11 weeks. Doenjang consumption alleviated hippocampal neuronal loss, which was increased by the HF diet. Accordingly, we observed higher cell proliferation and neurotrophic factor mRNA levels in the DJ group. Contents of oxidative metabolites and mRNA levels of oxidative stress- and neuroinflammation-related genes were lower in the DJ group compared to the HF group. Dietary doenjang reduced β-amyloid peptide (Aβ) levels by regulating gene expressions involved in Aβ production and degradation. Furthermore, doenjang consumption reduced tau hyperphosphorylation induced by HF feeding. Overall, doenjang was more effective than steamed soybean in suppressing neuroinflammation and neurodegeneration in mice fed an HF diet. These results suggest that bioactive compounds produced during the fermentation and aging of soybean may be involved in the enhanced neuroprotective effects of doenjang.